2018
DOI: 10.1038/s41598-018-32720-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of bioelectrical properties of cancerous tissue in advanced epithelial ovarian cancer patients

Abstract: Currently, there are no valid pre-operatively established biomarkers or algorithms that can accurately predict surgical and clinical outcome for patients with advanced epithelial ovarian cancer (EOC). In this study, we suggest that profiling of tumour parameters such as bioelectrical-potential and metabolites, detectable by electronic sensors, could facilitate the future development of devices to better monitor disease and predict surgical and treatment outcomes. Biopotential was recorded, using a potentiometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Our results show that tumor spread has a strong correlation with the EPD between tumor and paratumor, and patients with positive V Tumor–Paratumor have higher rates to develop tumor spread. This is consistent with a recent study that showed that high tumor potential value was correlated with the advanced stage of epithelial ovarian cancer 28 . Additionally, CD44+ CSCs showed directional migration toward the negatively charged substrate.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results show that tumor spread has a strong correlation with the EPD between tumor and paratumor, and patients with positive V Tumor–Paratumor have higher rates to develop tumor spread. This is consistent with a recent study that showed that high tumor potential value was correlated with the advanced stage of epithelial ovarian cancer 28 . Additionally, CD44+ CSCs showed directional migration toward the negatively charged substrate.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with a recent study that showed that high tumor potential value was correlated with the advanced stage of epithelial ovarian cancer. 28 Additionally, CD44+ CSCs showed directional migration toward the negatively charged substrate. We also observed that a higher abundance of CD44+ CSCs was observed in patient paratumor tissue when V Tumor-Paratumor was positive.…”
Section: Directional Migration Of Cscs In Charged Matrigelmentioning
confidence: 99%
“…[92] Similarly, a high tumor bioelectric potential was correlated with advanced tumor stage in patients with epithelial ovarian cancer. [93] Therefore, the change in potential caused by gene expression level or activity of ion channels is evolving as a new hallmark for the diagnosis of cancer. New bioelectronic devices that could monitor these bioelectric changes could revolutionize the point-of-care diagnostic tool for rapid and early detection of cancer.…”
Section: Detecting and Monitoring Tumors Based On Electrical Activitymentioning
confidence: 99%
“…For instance, microelectrodes and neutralized input capacity amplifiers have been used for intracellular potential measurements, [98] high-impedance micropipettes have been used to show a measured difference in V m of normal and cancerous fibroblasts and hepatocytes, [86] and a potentiometry based method has been developed using a combination of a Ag/AgCl and tungsten electrode to measure the bioelectric potential of non-cancerous and cancerous omental tissue in patients with advanced ovarian cancer. [93] Electrical impedance spectroscopy (EIS) is also capable of detecting altered electric properties of normal versus cancerous tissues of different types. [99][100][101] Some electronic sensors are also able to assess the aggressiveness of tumor cells.…”
Section: Detecting and Monitoring Tumors Based On Electrical Activitymentioning
confidence: 99%
“… 24–27 In fact, the ability to continuously and frequently monitor other solid and heterogeneously evolving tumors (eg, epithelial ovarian cancer) has provided clinical benefits in the form of more informed (and effective) treatment plans, and improved median overall survival. 28 , 29 The emerging liquid biopsy approach, while showing promise for tumor sequencing and early-stage detection, 30 , 31 is currently limited to use as a correlative tool alongside traditional biopsy, mostly due to the scarcity of brain tumor material available in blood and CSF. 9 , 13 This means that the sensitivity required to find and evaluate the minimal amount of useful material will be prohibitively high.…”
Section: Discussionmentioning
confidence: 99%